On Bénard convection in a porous medium in the presence of throughflow and rotation in hydromagnetics - Sunil; Bharti, P.K.; Sharma, R.C. (Archives of Mechanics, 2003)
The effect of throughflow on a layer of a rotating fluid heated from below in porous medium in the presence of vertical magnetic field is considered. For the case of stationary convection, the rotation has always a stabilizing effect. The medium permeability has always a destabilizing effect whereas the magnetic field and the throughflow have always a stabilizing effects in the absence of rotation. But in the presence of rotation, the medium permeability is found to have a destabilizing effect whereas the magnetic field and the throughflow have a stabilizing effects under certain conditions. Graphs have been plotted by giving numerical values to the parameters, to depict the stability characteristics. The magnetic field and rotation introduce oscillatory modes in the system, which were nonexistent in their absence. The sufficient conditions for non-existence of the overstability are also obtained.